The Transactional Origins of Authors’ Copyright - Curtin, Rebecca Schoff (The Columbia Journal of Law & the Arts, 2017)
One of the paradoxes of copyright history is that the Statute of Anne, which nominally recognized authors’ copyright for the first time, did not much change the day-to-day business of the Stationers who had previously enjoyed a virtual monopoly on the legal right to copy and who had also lobbied in support of the statute. This Article posits that commercial practice continued as it had because the concept of authors’ copyright had already begun to form in the contracts between authors and their publishers prior to the Statute’s enactment. These transactions, in some cases, gave authors greater rights in their work than the legal default required. Experience in the marketplace helped to assure both authors and booksellers that licensing transactions could support the creation and distribution of books in a world in which, going forward at least, authors would hold copyright in their new works. Commercial practice informed legal theory at this critical juncture in history and helped to change the legal and social norms associated with copyright. This Article draws on the records of the Stationer’s Company, parliamentary journals, and rarely seen, unpublished contracts from the eighteenth century and before to uncover the practical, transactional origins of authors’ copyright in England.